Penerapan Akuntansi Aset Biologis Berdasarkan PSAK 69 Pada Perusahaan Sektor Peternakan Di Indonesia: PT Widodo Makmur Perkasa TBK - Dewi Nur Aisyah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Livestock is a type of business that carries out activities of breeding or raising livestock. Companies engaged in the livestock sector have inventories or assets that are one of their characteristics, namely assets or livestock supplies, commonly referred to as biological inventories or assets. The accounting standard governing biological inventory or assets is Statement of Financial Accounting Standards 69 (PSAK 69) regarding Agriculture. The application of this accounting standard has many impacts on companies that apply it, but there are still many companies that do not apply this accounting standard and prefer to use the old accounting standards. This study aims to find out how the consequences or impacts arise from the implementation of PSAK 69 with the sample used is the company Widodo Makmur Perkasa Tbk as one of the companies that have implemented this accounting standard. The data used can be taken from the annual financial reports of the Company Widodo Makmur Perkasa Tbk on the website https://widomakmurperkasa.co.id for 2020 and 2021. The results received are in accordance with the results of research that has been carried out, one of which is the research conducted by Mohamad Dedi Junaedi in 2021 regarding "Biological Asset Accounting - Case Study of Pt. Seeds of Indonesia, namely the application of PSAK 69 has a significant impact on a company's financial reporting such as adding accounts and changes in the amount of current assets.